2019
DOI: 10.15294/kemas.v14i3.15753
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Technical Guidance for Public Health Center Officer Based on Training Evaluation

Abstract: Health promotion services at public health center is essential to support healthy behavior but still many officers did not have the competence and quality to conduct standard health promotion. West Java implemented health promotion training to 238 officers from 10 districts. The research objective was determining changes in participants’ knowledge and its implementation after training as a basis for sustainable technical guidance. Mixed methods design explanatory sequential as results from training analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…Publisher: Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu ini masih memiliki kelemahan yaitu belum dilakukannya pengukuran keterampilan dengan metode observasi langsung pelaksanaan keterampilan sewaktu menjalankan tugas di lapangan. Saran penelitian selanjutnya adalah mengembangkan model peer evaluation (evaluasi teman sejawat) atau supervisor evaluation (evaluasi supervisor lapangan) dengan melakukan observasi pelaksanaan pelaksanaan keterampilan sewaktu menjalankan tugas di lapangan yang bisa dikembangkan menjadi model pembinaan dan evaluasi berkelanjutan, seperti yang dikemukakan dalam penelitian terdahulu perlunya pembinaan dan evaluasi berkelanjutan bagi petugas promosi kesehatan Puskesmas (33). Penelitian lainnya adalah melakukan evaluasi level 4 model Kirkpatrick's yaitu mengevaluasi hasil yaitu efek terhadap kinerja organisasi.…”
Section: Kesimpulanunclassified
“…Publisher: Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu ini masih memiliki kelemahan yaitu belum dilakukannya pengukuran keterampilan dengan metode observasi langsung pelaksanaan keterampilan sewaktu menjalankan tugas di lapangan. Saran penelitian selanjutnya adalah mengembangkan model peer evaluation (evaluasi teman sejawat) atau supervisor evaluation (evaluasi supervisor lapangan) dengan melakukan observasi pelaksanaan pelaksanaan keterampilan sewaktu menjalankan tugas di lapangan yang bisa dikembangkan menjadi model pembinaan dan evaluasi berkelanjutan, seperti yang dikemukakan dalam penelitian terdahulu perlunya pembinaan dan evaluasi berkelanjutan bagi petugas promosi kesehatan Puskesmas (33). Penelitian lainnya adalah melakukan evaluasi level 4 model Kirkpatrick's yaitu mengevaluasi hasil yaitu efek terhadap kinerja organisasi.…”
Section: Kesimpulanunclassified
“…Indicators and measurements of the impact of community action require precise definitions of ongoing environmental (organizational, community, social) and individual changes as part of program objectives (TAIoPC, 2008). Modules or guidelines should be developed for direct technical guidance by referring to the curriculum, training module, and health promotion implementation policy (Surtimanah et al, 2019).…”
Section: Claritymentioning
confidence: 99%
“…This study aimed to find out the in-depth views of Muhammadiyah members in Jakarta towards the third edition of the COVID-19 guidelines issued by the MCCC with respect to consistency, clarity, relevancy, credibility, and interest points of view. Surtimanah et al (2019) evaluated the guidelines for Quick Medical and Public Health handling of Coronavirus Disease (COVID-19), and they observed that the guidelines were not suitable since they were less attractive to the public and difficult to understand. Health workers' understanding of the guidelines for rapid medical and public health handling of COVID-19 in Indonesia was good but on the contrary difficult for the public to understand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation